PQ, DQ and CPT control methods for shunt active compensators - A comparative study - Mortezaei, Ali; Lute, Christopher; Simões, M. Godoy; Marafão, Fernando P. [UNESP]; Boglia, Alessandro [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This paper investigates three different control techniques for controlling shunt active compensators for harmonic, reactive power and unbalance compensation. The considered methods were the instantaneous real and imaginary power theory (PQ), the Conservative Power Theory (CPT) and the synchronous reference frame method (DQ). So, the major goal is to explore the main similarities and differences in terms of steady state performance, dynamic response and computational complexity of each compensation method. Additionally, the paper also discusses how to achieve selective compensation by means of every technique, by means of suitable power and current decompositions. A three-phase grid with unbalanced non-linear load and non-negligible line impedance was used for comparing the approaches under ideal and deteriorated voltage conditions.